Correlation between Functional Disorders of Temporomadibular Joint and Upper Crossed Syndrome - Vilma Juodžbalienė; Dovilė Krasauskytė; Dovilė Valatkienė (Lithuanian Sports University, 2019)
Research background. The imbalance between the jaw and neck muscle activity occurs as a compensatory mechanism in order to stabilize the jaw and neck structural parts in temporomandibular joint (TMJ) disorders (Ries et al., 2008). Changes occur in posture control system if any biomechanical unit varies (Ritzel et al., 2007). One system compensates the unusually active other body system in upper cross syndrome (UCS) (Tharcher et al., 2011). This syndrome is characterized by shortened upper trapezius, pectoralis major and romboids and week middle and lower trapezius, serratus anterior and deep neck ﬂexors (Moore, 2004; Tharcher et al., 2011). Thus, it is believed that there may be a direct link between the upper cross syndrome and temporomandibular joint dysfunction. Purpose. Explore relationship between temporomandibular joint dysfunction and upper crossed syndrome in women. Methods. Thirty female volunteers participated in the study, and they were divided into groups according to trigger points in the shoulder and neck muscles: group 1 - painful shoulder and neck muscles (32.65 ± 12.34 years), group 2 - painless shoulder and neck muscles (34.5 ± 10.95 years). Survey was carried out assessing TMJ function during observation, palpation, evaluation of the sagittal craniovertebral angle, the neck and shoulder muscle length, strength, pain and deep neck muscle endurance was examined. Results. It was found that TMJ function was strongly associated with the UCS: trapezius pain as well as upper trapezius and scalenus length. TMJ disorders were associated with headache in both groups. Weak connection between deep neck muscle endurance and TMJ dysfunction was identifed. Conclusions. TMJ mobility is partly related to UCS, and TMJ functional disorders related to headache and sagittal craniovertebral angle. UCS specifc changes, such as pectoralis muscle length changes and impaired deep neck muscle endurance are not related to TMJ dysfunction. Keywords: temporomandibular joint, the upper crossed syndrome, muscle length, headache.